Morphometric analyses of Neyyar River Basin, southern Kerala, India. Issue 4 (2nd October 2017) - Dinagara Pandi, P.; Thena, T.; Nirmal, B.; Aswathy, M. R.; Saravanan, K.; Mohan, K.
Abstract: The natural behaviour of the earth's surface is proceeding through morphometric analyses and its environmental aspects. Different aspects of morphometric analyses depends upon geological transformation of earth surface. The structure of landscape determines the river flow from upper to lower elevation. The morphometric studies of river integrates the new geo morphological features with the climatic factors such as rainfall, temperature, atmospheric pressure and wind. The drainage map is prepared using the toposheets, delineating the streams and watershed boundary. The strahler method classifies the stream orders for this sophisticated morphometric analyses. The quantitative morphometric analysis carried out in Neyyar sub-watershed includes Network analysis; Basin geometry; Texture analysis and Relief characteristics. The relief characteristics were used to generate the hypsometric curve which exhibit the monadnock and reliefs of coastal morphology. Drainage, Drainage Density, Geomorphology, Landuse/Landcover, and Slope were prepared using Geographic Information Systems (GIS). The present study concludes the influence of the parameters and thematic data in understanding the geomorphological problems and stating a sustainable development of water resources in Neyyar sub-watershed.